How Representative are Insomnia Clinical Trials? - Roehrs, T. (Sleep Med, 2018)
STUDY OBJECTIVES: To address the question of how representative subjects studied in hypnotic clinical trials are of the broader insomnia population, this study assessed initial contact rates and reasons for inclusion and exclusion during recruitment to an efficacy trial and to a safety trial of Food & Drug Administration (FDA) approved hypnotics. METHODS: Otherwise heathy persons meeting Diagnostic Statistical Manual, Fourth Edition, Revised (DSM-IVR) criteria for insomnia were recruited. In one study, persons 32-65 yrs, were invited to a 12 month trial of nightly use of zolpidem or placebo. In the other persons 21-64 yrs with driver’s licenses were recruited to test the effects of a hypnotic on live on-the-road driving ability. In both studies screening was conducted through an initial telephone interview followed by a clinic visit. RESULTS: In the United States (US) study 13% (n=410) of 3180 initial contacts and in the Netherlands (NL) study 67% (n=53) of the 79 initial contacts proceeded to the clinic visit. Of those at clinic 25% of US and 37% of NL participants failed to meet additional insomnia criteria. Mental health exclusions accounted for 24% of US and 23% of NL participants and medical problems accounted for 23% of US and 9% NL exclusions. Finally 20% of US and 26% of NL participants were excluded for drug use/abuse histories. After all screening 4% of the initial US contacts and 0% of the NL contacts entered the study. CONCLUSIONS: These data suggest persons entering insomnia hypnotic clinical trials are a highly selected sample that is unlikely to be representative of the broad insomnia population or the population of potential medication users.